If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 36 = 6x + 18 Reorder the terms: 36 + 9x = 6x + 18 Reorder the terms: 36 + 9x = 18 + 6x Solving 36 + 9x = 18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 36 + 9x + -6x = 18 + 6x + -6x Combine like terms: 9x + -6x = 3x 36 + 3x = 18 + 6x + -6x Combine like terms: 6x + -6x = 0 36 + 3x = 18 + 0 36 + 3x = 18 Add '-36' to each side of the equation. 36 + -36 + 3x = 18 + -36 Combine like terms: 36 + -36 = 0 0 + 3x = 18 + -36 3x = 18 + -36 Combine like terms: 18 + -36 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| F(x)=-1(x+1)(x-7) | | 3x+37=11.25 | | -18x+31=-12x+19 | | cos70=14/x | | 48-4x=7x | | 2-(x+1)=2x-11 | | 6(3x-2)=3-2(4x+1) | | -9x+9=-6x+6 | | m/2=27 | | 7x+4=7(8)+4 | | 6(w-2)=-7w-25 | | 19x-79=12x-44 | | 8(-2x+3)=32 | | 80-2x=50 | | x-.3x=38000 | | -15x-125=-9x-83 | | -3k^2=-75 | | 6a^2-8ab=0 | | -4x+14y=2 | | -6x+25=-3x+13 | | 3p-14=p | | 18=2t+8 | | -3x-3=-2x-2 | | x^2-88=-7 | | 0.09xX=123.42 | | 11x+21=6x+11 | | p/7=28 | | 15x+50=9x+32 | | 2(3x-4)=7(2x+5) | | 3-(x+2)=1 | | -r/3≤6 | | 28=p/7 |